Bangladesh: Un país de gente que ama la belleza - Sala Baez, Yolanda (2005)
The autor present a brief description of a country characterized by capitalist modernity at the beginning of the century XXI. From the perspective of Cultutal Antropology she describes and analyzes the changes occured in the urban oand rural landscape. Using observation and interviews she transmits to us the expressions snd the emotions of the inhabitants from Bangladesh.